Initial Experience of Using Polymyxin B Hemoperfusion in Abdominal Septic Shock: Things to Consider for Better Outcome - Young Jun Park; Eun Young Kim (Journal of Acute Care Surgery, 2020)
Purpose Polymyxin B hemoperfusion (which treats septic shock by removing endotoxins of gram-negative bacteria), has been proposed as a treatment modality for intraabdominal sepsis. However, there are few studies about the factors that need to be taken into consideration for a better outcome. The aim of this study was to assess the effectiveness of polymyxin B hemoperfusion in abdominal septic shock and analyze the factors affecting the outcome of this therapy. Methods A retrospective review was performed in 41 patients who were diagnosed with abdominal septic shock. There were 12 patients treated with polymyxin B hemoperfusion, and 29 patients treated with conventional therapy. The clinical outcomes of the 2 groups were compared to identify the factors affecting the outcome of hemoperfusion. Results The decrement of vasopressor requirement represented by vasopressor dependency index was 2.5 in the hemoperfusion group and 0.1 in the conventional therapy group (p = 0.021), and in-hospital mortality was 33.3% in the hemoperfusion group and 69.0% in the conventional therapy group (p = 0.045). In logistic regression analysis, hemoperfusion was identified as a factor reducing in-hospital mortality in patients with sufficient source control, but not in patients with insufficient source control. In patients who had undergone hemoperfusion, the longer time to initiate hemoperfusion was identified as a risk factor of in-hospital mortality (p = 0.039). Conclusion Polymyxin B hemoperfusion may be an effective therapy for treating abdominal septic shock, and early use of this modality with definite source control might be important for a better outcome.